1999
DOI: 10.1063/1.369329
|View full text |Cite
|
Sign up to set email alerts
|

Intervalence band absorption in InP

Abstract: We have calculated intervalence band absorption loss coefficients for InP with various hole densities at 297 and 400 K. The calculated values agree well with the reported measured values at 297 K. However, the calculated values are much smaller than the reported measured values at 400 K. We discuss the difference between our calculated values and the reported calculated values at 297 K and the discrepancy between our calculated values and the reported measured values at 400 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The reflectance and transmittance spectra were used to derive ε(ω) using the fitting procedure. The value of ε ∞ (9.6) was taken as a fixed parameter [12]. The ω p for FC with effective mass (m * ) and carrier concentration (n p ) can be found by…”
Section: Drude and Lorentz Model For Free-carrier Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflectance and transmittance spectra were used to derive ε(ω) using the fitting procedure. The value of ε ∞ (9.6) was taken as a fixed parameter [12]. The ω p for FC with effective mass (m * ) and carrier concentration (n p ) can be found by…”
Section: Drude and Lorentz Model For Free-carrier Absorptionmentioning
confidence: 99%
“…Infrared absorption in GaP [10] and InP [11] bulk crystals has been reported previously using two-phonon absorption spectroscopy, which also discuss the effect of higher-order terms of the primary phonons of those materials. A few studies have been reported based on density matrix theory [12] in the near-IR (1-3 µm) region for InP epitaxial films. However, detailed mid (3-14 µm) and far (14 µm and beyond) IR absorption (experimental or theoretical) studies for p-InP epitaxial films have not been reported, and also have not been modeled using the DF.…”
Section: Introductionmentioning
confidence: 99%
“…These deficiencies are the most likely reasons behind poor quantitative agreement between the IVBA spectra calculated within the framework of the Kane model and experimental data. [6][7][8][9] Valence band energy spectra and dipole matrix elements for intervalence band optical transitions both can be described more accurately with another popular k-p method, based on the Luttinger-Kohn model. 14 In this model, some mixing effects due to all other bands are included through several phenomenological parameters.…”
Section: Formulation Of Ivba Coefficientmentioning
confidence: 99%
“…5 Although the role that IVBA plays in the longwavelength devices has been understood for quite a number of years, it is difficult to find an adequate model for this phenomenon in the literature that is suitable for device simulation. Often one or more of the following problems with the calculated spectra exist: the magnitude or slope is too high, 6,7 the temperature dependence is wrong, 8 or the models are heavily empirical. 1,3,9,10 Several possible solutions to these problems have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…in infrared ͑IR͒ radiation fields. [13][14][15][16][17][18] In this paper we shall be interested in the excitation of valence-band holes by highintensity femtosecond IR laser fields.…”
Section: Introductionmentioning
confidence: 99%